Emergence of university-centred entrepreneurial ecosystems in the Caribbean. Issue 4 (August 2019) - Allahar, Haven; Sookram, Ron
This study examines the progress of the two major universities in the Caribbean country of Trinidad and Tobago towards the transition to entrepreneurial universities through incorporating the core components of designing and delivering entrepreneurship education programmes, establishing effective university-led business incubators and the building of university–industry–government collaboration. The theoretical construct of the Triple Helix interrelationships and the development stages framework provide the basis for analysing the progress of the universities towards achieving their development mission. The general conclusion is that progress towards building an effective university-centred entrepreneurial ecosystem has been relatively slow and needs to be accelerated through more proactive leadership and greater involvement of internal and external stakeholders.